LEVEL OF STUDENT TRAVELER SATISFACTION FACULTY OF ECONOMICS AND BUSINESS UKI TO QUALITY OF TRAVELOKA SERVICES - Sautman Sinaga; Ktut Silvanita Mangani; Iman , Jaka (Fundamental Management Journal, 2020)
Currently the tour and travel business in Indonesia has experienced a rapid increase. This is seen from the high interest of Indonesian travelers to travelThis research is quantitative, the sample taken is active students in the even semester of the Faculty of Economics and Business, Indonesian Christian University, as many as 96 respondents. To measure the level of satisfaction of traveloka consumers, a performance analysis and performance of the Cartesian diagram is used, and the variables used in this study are professionalism and skills, attitudes and behavior, accessibility and flexibility, reliability and trustworthiness, recovery and reputation and credibility. Keywords : professionalism and skills, attitudes and behavior, accessibility and flexibility, reliability and trustworthiness, recovery and reputation and credibility, customer satisfaction and services quality